Morphometric variation of five dominant parrotfish (Scaridae) harvested from the Northern Waters of Aceh - Nanda Ulfa Khaira; ZA Muchlisin; Nur Fadli (Depik, 2025)
The waters of Aceh are surrounded by three major water bodies: the Andaman Sea, the Indian Ocean, and the Malacca Strait. Differences in current patterns extend the distribution range and contribute to the species diversity. Fish from the Scaridae family are among the species that thrive in these environments. The family Scaridae (Rafinesque 1810), commonly known as parrotfish, inhabits tropical seas, including the Pacific, Indian, and Atlantic Oceans, and is often found in coral reef areas. Parrotfish play a crucial role in maintaining coral reef health as one of the herbivorous fish species. This study aims to analyze the morphometric variation of five parrotfish species harvested from the Northern waters of Aceh. Traditional morphometrics using 12 measurement characters were applied to 60 fish samples from five species of the Scaridae family (Chlorurus capistratoides, Chlorurus sordidus, Scarus ghobban, Scarus niger, and Scarus rubroviolaceus). The results showed that Scarus rubroviolaceus shares four similar characters with Scarus ghobban: ED, HL, CPL, and PFL; it also shares four characters with Scarus niger: ED, HL, CPL, and SNL. Chlorurus capistratoides shares three similar characteristics with Scarus niger: CPL, ED, and PFL. In addition, the results of the DFA analysis revealed that Scarus ghobban and Scarus niger exhibit the highest degree of similarity in morphometric traits, particularly in HL, SNL, DFBL, ED, and PFL. Furthermore, Scarus rubroviolaceus demonstrates a slight overlap with Chlorurus capistratoides, while Scarus niger shows a minor overlap with Scarus rubroviolaceus. This study provides morphological diversity of parrotfish species in the northern Aceh waters.Keywords:Aceh watersmorphometricsParrotfishMeasurement charactersDFA